Integrating Ultra-Weak Photon Emission Analysis in Mitochondrial Research - Van Wijk, Roeland; Van Wijk, Eduard P.A.; Pang, Jingxiang; Yang, Meina; Yan, Yu; Han, Jinxiang (Frontiers in Physiology, 2020)
Once regarded solely as the energy source of the cell, nowadays mitochondria are recognized to perform multiple essential functions in addition to energy production. Since the discovery of pathogenic mitochondrial DNA defects in the 1980's, research advances have revealed an increasing number of common human diseases which share an underlying pathogenesis involving mitochondrial dysfunction. A major factor in this dysfunction are reactive oxygen species (ROS) which influence the mitochondrial-nuclear crosstalk and the link with the epigenome, an influence that provides explanations for pathogenic mechanisms. Regarding these mechanisms, we should take into account that mitochondria produce the majority of ultra-weak photon emission (an aspect that is often ignored) -this type of emission may serve as a non-invasive assay for oxidative radical reactions, thus providing new opportunities for diagnosis and prevention of mitochondrial dysfunction. In this article, we will overview three relevant areas of mitochondria-related research over the period 1960 -2020: (a) respiration and energy production, (b) respiration related production of free radicals and other ROS species, and (c) ultra-weak photon emission in relation to ROS and stress. First, we will outline how these research areas initially developed independently of each other 2 -following that, our review aims to show their stepwise integration during later stages of development. It is suggested that a further development of integrated mitochondrial research has the potential to enhance the progress of modern medicine.